New Polyketides from the Antarctic Fungus Pseudogymnoascus sp. HSX2#-11 - Ting Shi; Yan-Yan Yu; Jia-Jia Dai; Yi-Ting Zhang; Wen-Peng Hu; Li Zheng; Da-Yong Shi (Marine Drugs, 2021)
The species Pseudogymnoascus is known as a psychrophilic pathogenic fungus with a ubiquitous distribution in Antarctica. Meanwhile, the study of its secondary metabolites is infrequent. Systematic research of the metabolites of the fungus Pseudogymnoascus sp. HSX2#-11, guided by the method of molecular networking, led to the isolation of one novel polyketide, pseudophenone A (1), along with six known analogs (2–7). The structure of the new compound was elucidated by extensive spectroscopic investigation and single-crystal X-ray diffraction. Pseudophenone A (1) is a dimer of diphenyl ketone and diphenyl ether, and there is only one analog of 1 to the best of our knowledge. Compounds 1 and 2 exhibited antibacterial activities against a panel of strains. This is the first time to use molecular networking to study the metabolic profiles of Antarctica fungi.